STUDENTS PERCEPTION ON SCHOOL COEXISTENCE: A STUDY ON CONTRIBUTIONS OF SUPPORT SYSTEMS BETWEEN EQUALS (SAIS) IN BRAZILIAN AND SPANISH SCHOOL INSTITUTIONS - Paulino Tognetta, Luciene Regina [UNESP]; Martinez Aviles, Jose Maria; Souza, Raul Alves de [UNESP]; Duarte, Lidia Morcelli; Nadai, Sandra Trambaiolli de [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
The world literature has indicated more effective ways of prevention and intervention to bullying and its consequences in school. They are strategies that rely on the quality improvement of the school climate and the implementation of Support Systems between Equals (SAI). The present research seeks to verify students' perceptions regarding the quality of coexistence in schools with and without the implementation of a type of SAI called Help Teams(HT), a Spanish model adapted to the Brazilian schools. For that, a field research was carried out, with an exploratory and descriptive character, using a questionnaire between students from Brazil and Spain. Participated in this investigation 756 students of Brazilian Schools, 454 with the HT and 302 without HT and 438 Spain, 243 with HT and 195 without HT. The results show better quality in interpersonal relationships in schools with Help Teams. However, comparing the perception of the interpersonal relations of students from Brazilian and Spanish, even in Brazilian schools with SAI implemented, there are more problems than in Spanish schools that do not have such a model of work with the students. Although the coexistence theme is present in the Brazilian Law, the model is still recent and there are no public policies for the educational programs implementation to prevent these problems as in Spain.
Keywords: Coexistence; Support Systems between Equals (SAIs); Bullying